Vascular complications and associated comorbidities in newly diagnosed pre-diabetes: is it the tip of the iceberg? - Genc, S.; Evren, B.; Cankaya, C.; Tecellioglu, M.; Bozbay, A.; Yavuz, A. O.; Sahin, I. (Verduci Publisher, 2023)
OBJECTIVE: The aim of this study was to investigate the prevalence of microvascular and macrovascular diabetic complications and the associated comorbidities in newly diagnosed pre-diabetic individuals. PATIENTS AND METHODS: This cross-sectional study includes 100 newly diagnosed pre-diabetic individuals. Fasting plasma glucose, HbA1c, and oral glucose tolerance (OGTT) were tested according to the American Diabetes Association's diagnostic criteria for pre-diabetes, besides anthropometric measurements, lipid profiles, and demographic and biochemical parameters. Comorbidities like hypertension, obesity, dyslipidemia etc., were evaluated. All participants were screened for microvascular (retinopathy, nephropathy, neuropathy) and macrovascular [coronary artery disease (CAD) and cerebrovascular event-peripheral artery disease] complications. RESULTS: Microvascular complications were found in 12% of the participants (neuropathy: 4%, nephropathy: 8%) and 19% had macrovascular complications. Of the participants, 21% of the cases presented hypertension, 21% dyslipidemia and 48% obesity. A high probability of developing non-alcoholic fatty liver disease- related fibrosis [estimated using non-alcoholic fatty liver disease fibrosis score (NFS)] was found in 68% of cases. History of dyslipidemia (OR: 5.00, 95% CI: 1.10-22.56; p = 0.037) was an independent risk factor for the development of vascular complications. CONCLUSIONS: Diabetic vascular complications were found in approximately one-third of pre-diabetic cases. Dyslipidaemia was found to be an important risk factor for the development of vascular complications in these individuals.
Keywords: Prediabetes; Diabetic complications; Microvascular; Macrovascular; Comorbidities; Risk factors